Retinoblastoma in South Asia: A Scoping Review - Roland Joseph D. Tan; Denzel C. Umerez; Jasper Ian A. Alindayu; Jose Manuel Ricardo M. Conjares; Daniel Alexander D. Go; Reynaldo Gabriel T. Paulino (Asian Pacific Journal of Cancer Care, 2021)
Introduction: Pakistan, Indonesia, Bangladesh and the Philippines are listed as among the six Asian countries which will be the sources of 43% or almost 4000 new cases of the estimated world’s retinoblastoma cases in 2023. Materials and Methods: Scoping review of literatures using the databases of Pubmed, EMBASE, Scopus, Science Direct, Google scholar and Web of Science databases as well as local and regional databases on clinical features, treatment and outcomes of retinoblastoma patients from Pakistan, Indonesia, Bangladesh and the Philippines was done. A descriptive analysis using the 2017 retinoblastoma database of the Global Retinoblastoma Study Group (GRSG) was added to supplement data for Bangladesh, Indonesia and the Philippines. Results: A total of 17 articles were included in this review. There were 696 retinoblastoma patients involving at least 859 eyes seen in Pakistan from 1997 to 2018 and included in the 7 articles reviewed. There were 617 retinoblastoma patients involving at least 677 eyes seen in Indonesia from 2003 to 2018 and included in the 8 articles reviewed and the GRSG’s database. There were 161 retinoblastoma patients involving 221 eyes identified in the descriptive analysis of the GRSG’s database for Bangladesh. And there were 226 retinoblastoma patients involving 297 eyes seen in the Philippines from 1998-2020 from the 2 articles from the Philippines and the GRSG’s database. Discussion: Lack of awareness on the disease, distant centers, expensive service and cultural unacceptability of treatment were the commonly cited reasons for late consult. However, non-standardized and poor clinical reporting and monitoring, and non-standardized treatment protocols were also contributory to the low survival rates. The current management outcomes of retinoblastoma from the four countries are alarmingly below par with developed countries, India and China. Conclusion: Although advances had been made in the management of retinoblastoma, delay in consultation which often leads to advanced disease was still common. This contributes to low survival rates in the four countries.